PENGEMBANGAN MEDIA ULAR TANGGA MATERI PERKALIAN DAN PEMBAGIAN BILANGAN CACAH KELAS IV SDN 182 PEKANBARU - Miftah Hussaidah S; Siti Quratul Ain; Fitriana Yolanda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to develop snakes and ladders media material for the system of multiplication and division of whole numbers for class IV SDN. This research was carried out using the ADDIE model development research method which consists of 5 stages starting from Analysis, Design, Development, Implementation and Evaluation (Analyze, Design, Development, Implementation, and Evaluation) but in this research, researchers only limited it to the development stage. Data collection techniques in this research were through interviews and questionnaires. Based on validation results with 5 validators, namely two material experts, two media experts and one module expert, the results were 92% with valid criteria